Diagnostic validity of dynamic salivary gland scintigraphy with ascorbic acid stimulation in patients with Sjögren's syndrome: Comparation with unstimulated whole sialometry - Dugonjić Sanja; Ajdinović Boris; Stefanović Dušan; Jauković Ljiljana (Vojnosanitetski Pregled)
Background/Aim. Beside many actual groups of classification criteria, uniform classification criteria for Sjögren’s syndrome (SS) are still missing. The ophtalmic component of SS is well defined. Criteria for classifying its oral component remain controversial. The fifth item of the European Union and the United States of America (EU-US) revised diagnostic classification criteria in 2002, is an objective evidence of xerostomia, diagnosed by one of the tests: unstimulated whole sialometry (UWS), parotid sialography, and dynamic salivary gland scintigraphy (DSGS). The aim of this study was to evaluate senstitivity, specificity, positive and negative predictive value and accuracy of DSGS with ascorbic acid stimulation in detecting xerostomia in SS patients and to compare DSGS findings with UWS values. Methods. Tests DSGS and UWS were done in 20 patients with SS and in 10 of the control subjects. The findings of DSGS were graded from 1 to 4 scintigraphie (SCT) grade 1 - normal finding; SCT grade 2 - moderate function damage; SCT grade 3 - serious function damage, SCT grade 4 - very serious function damage. UWS measured 1.5 hour after the breakfast lasted 15 minutes. UWS bellow 2.5 ml/15min min. considered pathological. Results. All SS patients had pathological SCT findings. Comparing SCT grade between the patients and the control group, high statistical significance was found (p < 0.001). The estimated sensitivity of DSGS was 100%, specificity 80%, positive predictive value 91%, negative predictive value 100% and accuracy 93%. The calculated sensitivity of UWS was 75%. Salivary function damage detected by scintigraphy was in positive correlation with UWS findings. Conclusion. DSGS is a diagnostic test with high sensitivity, specificity, accuracy and positive and negative predictive values in detecting salivary function damage in SS patients. DSGS and UWS are very sensitive diagnostic tests for objective evidence of xerostomia, and have to be ones of the earliest investigations which should be performed in subjects suspected of SS. Test DSGS is more sensitive, and seems to better reflect symptoms of dry mouth than UWS.